On Durrmeyer Type Bernstein-Schurer Operators Defined by $(p, q)$-Integers (Analysis in Theory and Applications, 2025)
In this paper, we generalize the Durrmeyer-type Bernstein-Schurer operatorby applying $(p, q)$-integers and obtain uniform convergence of the operator. Furthermore, we deal with the approximation problems in terms of the modulus of smoothness and ${\rm K}$-functional. Finally, the operator is modified to get better estimation.